Rationale, Mission and Vision for a National Centre of Affective Disorders in Germany - Reif, Andreas; Baune, Bernhard T.; Deckert, Jürgen; Juckel, Georg; Kittel-Schneider, Sarah; Kircher, Tilo; Kornhuber, Johannes; Rupprecht, Rainer; Bauer, Michael (Pharmacopsychiatry, 2021)
Affective disorders are common, complex disorders representing one of the major challenges to global health in the 21st century. To mitigate the burden of disease, substantial public health efforts need to be undertaken since research on the causes and adequate treatment requires multidisciplinary approaches. These should integrate translational, and clinical research, aided by technological advancements in collecting and analysing comprehensive data. Here we present the rationale, concept, mission and vision of the recently founded National Centre of Affective Disorders (NCAD) in Germany. NCAD founding partners build on their previous successful cooperation within the German Research Network for Mental Disorders funded by the Federal Ministry of Education and Research (BMBF). They form an internationally pre-eminent network of integrative excellence, leading in science and contributing significantly to the improved care of affective disorder patients. The partners will provide complementary structures and innovative methods across the entire translational continuum from bench to clinical and real-world settings. The vision of the NCAD is to foster cross-disciplinary research from basic neuroscience to public mental health by close translational collaboration between academia, non-university research institutions, and international partners, including industry, to deliver cutting-edge research, innovative clinical services and evidence-based training to young clinicians and scientists. The mission is to accomplish research in a highly translational manner, especially with respect to clinical studies in a trans-sectoral way. This approach aims to ensure continuous improvement in the treatment and care provided to patients and an interdisciplinary environment for high-level research and education in affective disorders.
Keywords: affective disorders; bipolar disorder; major depression; anxiety; network